Assessment of spatial heterogeneity of employment in Russian regions - R. I. Vasilyeva; D. M. Ampenova (Вестник университета)
The article studies the problem of spatial heterogeneity of employment in Russian regions. Despite the rather high indicators for Russia and their positive dynamics, the situation in the regions is strikingly different. Heterogeneity of employment distribution between regions can be intensified as a result of the influence of some territories on others. The purpose of the study is to assess spatial heterogeneity and spatial autocorrelation effects between Russian regions in terms of employment. As the main research method, the paper applies Moran’s methodology to calculate local and global spatial autocorrelation indices and Anselin’s methodology to form a spatial matrix. The results of the study demonstrate that among Russian regions there is a high potential for clustering by the number of employed people. At the same time, a group of western regions is clearly distinguished, which have greater territorial cohesion characterized by pronounced spatial mutual influence. The results of the study can be used in formulating strategies for Russian regions development, in particular, the Far Eastern regions, as well as in determining priority development goals.